Mewujudkan etika dalam kegiatan perbankan syariah melalui penerapan prinsip tata kelola perusahaan yang baik - Yuristama, Agus Prakarsa; Saripudin, Udin (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The world of banking is an activity based on the principle of trust. The public will place their funds in a bank that is considered trustworthy. If factually, the Bank is not trusted, then whether the Bank will succeed in controlling the market share of public funds, of course this will be difficult. The concept of Islamic banking that carries Islamic values based on Allah's guidance in the Qur'an and the example of Rasulullah in the hadith will certainly be an effective tool in increasing public trust in placing their funds in Islamic banking. This study uses a qualitative approach. Good Corporate Governance according to the general view, as well as good Corporate Governance according to the philosophical view of Islam from the perspective of Ontology, Epistemology and Axiology in general are the same. The fundamental difference is actually the value of Islamic mysticism in good corporate governance according to the Islamic view. This difference clearly affects the perspective of good corporate governance. If it is based on an Islamic view, there needs to be an internalization of values because not all of the variables can be seen with the naked eye or reality.